Solid-state battery and method for manufacturing a solid-state battery
Patent Information
- Application Number
- JP2025059477
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166506000001
Abstract
Description
Technical Field
[0001] The present invention relates to a solid-state battery and a method for manufacturing the solid-state battery.
Background Art
[0002] In recent years, research and development on solid-state batteries that contribute to energy efficiency has been carried out to ensure that more people can access affordable, reliable, sustainable and advanced energy.
[0003] Patent Document 1 describes a solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer. Here, the negative electrode layer contains a borohydride compound.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of Invention
Problems to be Solved by the Invention
[0005] However, the solid-state battery described in Patent Document 1 may have a low initial Coulombic efficiency.
[0006] An object of the present invention is to provide a solid-state battery with high initial Coulombic efficiency.
Means for Solving the Problems
[0007] (1) A solid-state battery comprising: a negative electrode mixture layer containing a silicon-based active material and a solid electrolyte; and a solid electrolyte layer containing a sulfide solid electrolyte, wherein the solid electrolyte contained in the negative electrode mixture layer contains a boron cluster anion and a metal cation, and does not contain an organic cation.
[0008] (2) The solid electrolyte contained in the negative electrode mixture layer is represented by the general formula Li a (C b B c H d ) (wherein a is an integer of 1 to 5, b is an integer of 0 to 5, c is an integer of 1 to 20, and d is an integer of 1 to 20.) The solid-state battery according to (1), which is a lithium salt of a carborane anion represented by
[0009] (3) The lithium salt of the carborane anion includes Li(CB9H 10 ) and Li(CB 11 H 12 ), and the molar ratio of Li(CB9H 11 H 12 ) to Li(CB 10 ) is more than 0.1 and 10 or less, the solid-state battery according to (2).
[0010] (4) The solid-state battery according to any one of (1) to (3), wherein the negative electrode mixture layer has a content of the solid electrolyte of 20% by volume to 80% by volume.
[0011] (5) The solid-state battery according to any one of (1) to (4), wherein the negative electrode mixture layer has a volume ratio of the solid electrolyte to the silicon-based active material of 0.40 to 7.0.
[0012] (6) The solid-state battery according to any one of (1) to (5), wherein the negative electrode mixture layer further comprises a conductive aid.
[0013] (7) The solid-state battery according to (6), wherein the negative electrode mixture layer has a volume ratio of the conductive aid to the solid electrolyte of 0.010 to 0.30.
[0014] (8) The solid-state battery according to (6) or (7), wherein the conductive aid comprises carbon black.
[0015] (9) The solid battery according to any one of (1) to (8), wherein the negative electrode composite layer has a thickness of 10 μm or more and 200 μm or less.
[0016] (10) The solid battery according to any one of (1) to (9), wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.
[0017] A method for manufacturing a solid battery according to any one of (1) to (10), comprising the steps of: mixing a composition containing the silicon-based active material with the solid electrolyte at a temperature of 120°C or less to obtain a negative electrode composite material; and press-molding the negative electrode composite material to form the negative electrode composite layer. [Effects of the Invention]
[0018] According to the present invention, it is possible to provide a solid-state battery with high initial Coulomb efficiency. [Modes for carrying out the invention]
[0019] Embodiments of the present invention will be described below.
[0020] [Solid battery] The solid-state battery of this embodiment comprises a negative electrode composite layer containing a silicon-based active material and a solid electrolyte, and a solid electrolyte layer containing a sulfide solid electrolyte. Here, the solid electrolyte contained in the negative electrode composite layer contains boron cluster anions and metal cations, but does not contain organic cations. As a result, the initial Coulomb efficiency of the solid-state battery of this embodiment is high, and as a result, the energy density of the solid-state battery of this embodiment is high. The organic cation is not particularly limited, but examples include quaternary ammonium ions and phosphonium ions.
[0021] The solid electrolyte contained in the negative electrode composite layer is, in general terms, Li a (C b B c H d ) (In the formula, a is an integer between 1 and 5 (inclusive), b is an integer between 0 and 5 (inclusive), c is an integer between 1 and 20 (inclusive), and d is an integer between 1 and 20 (inclusive).) It is preferable that the lithium salt of the carborane anion represented by [formula] is used. This increases the initial Coulomb efficiency of the solid-state battery of this embodiment, even without melting the solid electrolyte when forming the negative electrode composite layer.
[0022] c is preferably d-1. In this case, d is preferably 5 to 15, and more preferably 8 to 14. Examples of lithium salts of carborane anions where c is d-1 include Li(CB7H8), Li(CB8H9), and Li(CB9H9). 10 ), Li(CB 10 H 11 ), Li(CB 11 H 12 ), Li(CB 12 H 13 ), Li(CB 13 H 14 ) are among them. From the perspective of productivity, Li(CB9H 10 ), Li(CB 10 H 11 ) and Li(CB) 11 H 12 ) is preferable.
[0023] The lithium salt of the carborane anion is Li(CB9H 10 ) and Li(CB 11 H 12 ) and Li(CB 11 H 12 Li(CB9H) 10 The molar ratio of ) is preferably greater than 0.1 and less than or equal to 10. This increases the initial Coulomb efficiency of the solid-state battery of this embodiment. At this time, Li(CB 11 H 12 Li(CB9H) 10 The molar ratio of ) is more preferably 0.2 or more and 5 or less.
[0024] The solid electrolyte content in the negative electrode composite layer is preferably 20% to 80% by volume, more preferably 25% to 75% by volume, and particularly preferably 40% to 70% by volume. When the solid electrolyte content in the negative electrode composite layer is 20% or more by volume, the ionic conductivity of the solid battery of this embodiment is increased, and when it is 80% or less by volume, the energy density of the solid battery of this embodiment is increased.
[0025] The volume ratio of the solid electrolyte to the silicon-based active material in the negative electrode composite layer is preferably 0.40 to 7.0, more preferably 0.50 to 4.0, and particularly preferably 0.70 to 2.5. When the volume ratio of the solid electrolyte to the silicon-based active material in the negative electrode composite layer is 0.4 or higher, the ionic conductivity of the solid battery of this embodiment is increased, and when it is 7 or lower, the energy density of the solid battery of this embodiment is increased.
[0026] The silicon-based active material is not particularly limited, but examples include elemental silicon, silicon alloys, silicon oxides, and composite materials containing silicon and other dissimilar elements. Examples of silicon alloys include SiC, SiN, SiTi, SiAl, SiLi, SiCu, etc., and examples of silicon oxides include SiO, etc. Examples of composite materials containing silicon and other dissimilar elements include silicon-lithium composite materials, silicon-carbon composite materials, silicon-aluminum composite materials, etc. The composite material containing silicon and other dissimilar elements may be a silicon alloy or not.
[0027] The negative electrode composite layer preferably further contains a conductive additive. This increases the initial Coulomb efficiency and initial discharge capacity of the solid-state battery of this embodiment.
[0028] The volume ratio of the conductive additive to the solid electrolyte in the negative electrode composite layer is preferably 0.010 or more and 0.30 or less, more preferably 0.10 or more and 0.30 or less, and particularly preferably 0.10 or more and 0.25 or less. If the volume ratio of the conductive additive to the solid electrolyte in the negative electrode composite layer is 0.01 or more, the electronic conductivity of the solid battery of this embodiment will be high, and if it is 0.30 or less, the energy density of the solid battery of this embodiment will be high.
[0029] The conductive additive is not particularly limited, but examples include carbon materials and metallic materials. Examples of carbon materials include carbon black, acetylene black (AB), Ketjenblack (KB), carbon nanotubes (CNT), metallic carbon nanotubes (MCNT), semiconducting carbon nanotubes (SCNT), and carbon nanofibers (CNF). Examples of metallic materials include Ni, Cu, Fe, and stainless steel (SUS). Examples of conductive material shapes include spherical and fibrous shapes. Among these, carbon black is preferred from the viewpoint of the initial Coulomb efficiency and initial discharge capacity of the solid-state battery of this embodiment.
[0030] The negative electrode composite layer may further contain a binder. The binder is not particularly limited, but examples include fluororesin-based binders such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), and fluororubber; and non-fluororubber-based binders such as butadiene rubber, hydrogenated butadiene rubber, styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, and ethylene propylene rubber. Alternatively, an acrylic binder may be used.
[0031] The thickness of the negative electrode composite layer is preferably 10 μm or more and 200 μm or less, more preferably 15 μm or more and 50 μm or less, and particularly preferably 15 μm or more and 40 μm or less. When the thickness of the negative electrode composite layer is 10 μm or more, the initial Coulomb efficiency of the solid-state battery of this embodiment is high, and when it is 200 μm or less, the energy density of the solid-state battery of this embodiment is high.
[0032] The negative electrode composite layer is preferably formed by mixing a composition containing a silicon-based active material and a solid electrolyte at a temperature of 120°C or lower to obtain a negative electrode composite, and then press-molding the negative electrode composite. This reduces the energy consumption when forming the negative electrode composite layer. At this time, the temperature at which the composition is mixed is more preferably 100°C or lower, even more preferably 80°C or lower, even more preferably 60°C or lower, and particularly preferably 40°C or lower. For example, the temperature at which the composition is mixed is 10°C or higher. The pressure when press-molding the negative electrode composite is not particularly limited, but for example, it is 1 MPa or more and 980 MPa or less. When mixing the composition, a small amount of dispersion medium may be added and wet mixing may be performed, but dry mixing is preferred.
[0033] The sulfide solid electrolyte contained in the solid electrolyte layer includes, for example, a metal element (M) that acts as a conductive ion and sulfur (S). Examples of M include Li, Na, K, Mg, and Ca. Among these, Li is preferred.
[0034] The sulfide solid electrolyte preferably contains Li, A (one or more elements selected from the group consisting of P, Si, Ge, Al, and B), and S, and more preferably Li and P. Furthermore, the sulfide solid electrolyte may further contain halogen elements (e.g., Cl, Br, I) from the viewpoint of ionic conductivity. The sulfide solid electrolyte may also further contain O.
[0035] Examples of the sulfide solid electrolyte include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (wherein m and n are positive numbers, and Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga or In), Li v P w S x Cl y Br z (v, w, x, y, z>0), and the like. Among these, Li v P w S x Cl y Br z (v, w, x, y, z>0) is preferable because the reaction resistance does not decrease even after repeated charge and discharge, and from the viewpoint of ion conductivity, Li v P w S x Cl y Br z (0<v<10, 0<w<5, 0<x<5, 0<y<5, 0<z<5) is more preferable, and examples thereof include Li 5.4 PS 4.4 Cl 0.8 Br 0.8 and the like.
[0036] The description of, for example, "Li2S-P2S5" means a sulfide solid electrolyte obtained using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.
[0037] Furthermore, the sulfide solid electrolyte may be sulfide glass or crystalline sulfide glass, or a crystalline material obtained by a solid-phase method. Sulfide glass can be obtained, for example, by performing a mechanical milling method (for example, a method of milling using a ball mill) on the raw material composition. Crystalline sulfide glass can be obtained, for example, by heat-treating sulfide glass at a temperature above its crystallization temperature.
[0038] The sulfide solid electrolyte contained in the solid electrolyte layer is preferably an argyrodite-type sulfide solid electrolyte. This increases the initial Coulomb efficiency and initial discharge capacity of the solid battery in this embodiment.
[0039] The form of the solid electrolyte is not particularly limited, but for example, particles can be used.
[0040] The solid electrolyte content in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more and 99% by mass or less.
[0041] The solid electrolyte layer may further contain a binder or the like.
[0042] The method for forming the solid electrolyte layer is not particularly limited, but one example is a method of press-molding a composition containing a sulfide solid electrolyte.
[0043] The thickness of the solid electrolyte layer is not particularly limited, but for example, it is between 0.1 μm and 1000 μm.
[0044] The solid-state battery of this embodiment further comprises, for example, a negative electrode current collector and a positive electrode. The solid-state battery is not particularly limited, but examples include all-solid-state lithium-ion secondary batteries and semi-solid-state lithium-ion secondary batteries.
[0045] The materials that make up the negative electrode current collector are not particularly limited, but examples include silver, palladium, gold, platinum, aluminum, copper, nickel, stainless steel, and carbon. Among these, copper, stainless steel, and nickel are preferred from the viewpoint of conductivity and cost.
[0046] The shape of the negative electrode current collector is not particularly limited, but examples include foil-like, plate-like, mesh-like, non-woven fabric-like, and foam-like forms.
[0047] The thickness of the negative electrode current collector is not particularly limited, but for example, it is between 0.1 μm and 1 mm.
[0048] For example, the positive electrode has a positive electrode composite layer formed on the positive electrode current collector.
[0049] The positive electrode composite layer contains a positive electrode active material. The positive electrode active material is not particularly limited, but examples include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and LiNi p Mn q Co r O2(p+q+r=1), LiNi p Al q Co r O2 (p+q+r=1), lithium manganese (LiMn2O4), Li 1+x Mn 2-x-y M y Examples include O4(x+y=2) (where M is one or more elements selected from the group consisting of Al, Mg, Co, Fe, Ni, and Zn), lithium titanate, and LiMPO4 (where M is one or more elements selected from the group consisting of Fe, Mn, Co, and Ni).
[0050] The content of positive electrode active material in the positive electrode composite layer may be 20% by mass or more, 30% by mass or more, or 40% by mass or more. On the other hand, the content of positive electrode active material in the positive electrode composite layer may be 99% by mass or less, 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0051] The positive electrode composite layer may further contain a solid electrolyte. The solid electrolyte is not particularly limited as long as it is capable of conducting lithium ions, but examples include oxide solid electrolytes and sulfide solid electrolytes.
[0052] The positive electrode composite layer may further contain a binder, a conductive additive, and the like.
[0053] The thickness of the positive electrode composite layer is not particularly limited, but for example, it is between 0.1 μm and 1000 μm.
[0054] The method for forming the positive electrode composite layer is not particularly limited, but one example is a method of applying a slurry containing a positive electrode active material and a solvent.
[0055] The material constituting the positive electrode current collector is not particularly limited as long as it is conductive, but examples include aluminum, aluminum alloys, stainless steel, nickel, iron, and titanium. Among these, aluminum, aluminum alloys, and stainless steel are preferred.
[0056] The shape of the positive electrode current collector is not particularly limited, but examples include foil-shaped and plate-shaped.
[0057] The solid-state battery of this embodiment can be manufactured by known methods. For example, the solid-state battery of this embodiment can be manufactured by laminating laminates in which a negative electrode current collector, a negative electrode composite layer, a solid electrolyte layer, a positive electrode composite layer, and a positive electrode current collector are sequentially laminated, and then press-molding them to integrate them.
[0058] Although embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and the above embodiments may be modified as appropriate within the scope of the spirit of the present invention. [Examples]
[0059] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.
[0060] [Example 1] The negative electrode composite layer, solid electrolyte layer, and half-cell were manufactured in a glove box purged with nitrogen as follows.
[0061] (Manufacturing of the negative electrode composite layer) Using a rotation-revolution mixer, the median diameter (D) is adjusted so that the volume ratio of the active material, solid electrolyte, and conductive additive is 29:64.5:6.5. 50 A negative electrode composite was obtained by dry mixing 32 parts by mass of 200 μm silicon (Aldrich), 57 parts by mass of lithium salt of carborane anion, and 11 parts by mass of carbon black at 25°C. At this time, the lithium salt of carborane anion was Li(CB9H 10 ) and Li(CB 11 H 12 The molar ratio with ) was 7:3, and it was not melted. Next, the negative electrode composite was press-molded at a pressure of 27 MPa to obtain a negative electrode composite layer with a thickness of 21.5 μm.
[0062] (Manufacturing of solid electrolyte layer) Median diameter (D 50 ) 700nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 The material was press-molded at a pressure of 27 MPa to obtain a solid electrolyte layer.
[0063] (Half-cell manufacturing) A cylindrical container with an inner diameter of 10 mm was sequentially laminated with copper foil, a negative electrode composite layer, a solid electrolyte layer, indium foil, lithium foil, and copper foil. After press molding at a temperature of 25°C and a pressure of 10 t, it was clamped in a SUS jig and restrained at a pressure of 60 MPa to obtain a half-cell.
[0064] [Example 2] Median diameter (D 50 A half-cell was obtained in the same manner as in Example 1, except that a silicon / carbon composite material was used instead of 200 μm of silicon (Aldrich). In this case, the anode composite layer had a thickness of 24.7 μm.
[0065] [Example 3] The volume ratio of the active material, the solid electrolyte, and the conductive auxiliary agent was adjusted to 40:50:10, and the median diameter D 50 )A half cell was obtained in the same manner as in Example 1, except that 44.5 parts by mass of 200 μm silicon (manufactured by Aldrich), 44.5 parts by mass of a lithium salt of a carborane anion, and 11 parts by mass of carbon black were dry-mixed. At this time, the thickness of the negative electrode composite material layer was 25.2 μm.
[0066] [Example 4] The volume ratio of the active material, the solid electrolyte, and the conductive auxiliary agent was adjusted to 50:40:10, and the median diameter D 50 )A half cell was obtained in the same manner as in Example 1, except that 54 parts by mass of 200 μm silicon (manufactured by Aldrich), 35 parts by mass of a lithium salt of a carborane anion, and 11 parts by mass of carbon black were dry-mixed. At this time, the thickness of the negative electrode composite material layer was 25.8 μm.
[0067] [Comparative Example 1] Li(CB9H 10 )A negative electrode was obtained in the same manner as in Example 2, except that 39.9 parts by mass and 17.1 parts by mass of Li(CB 11 H 12 )were replaced with an argyrodite-type sulfide solid electrolyte having a median diameter D 50 )of 700 nm (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 ). At this time, the thickness of the negative electrode composite material layer was 20.0 μm.
[0068] [Initial Coulomb Efficiency] A charge-discharge test of the half cell was carried out. Specifically, constant current charging was performed at 0.38 mA / cm 2 to -0.6 V, followed by a 10-minute pause, and then constant current discharging was performed at 0.38 mA / cm 2 to 0.9 V, and the initial Coulomb efficiency (the ratio of the initial discharge capacity to the initial charge capacity) was evaluated.
[0069] [Discharge capacity maintenance rate] Under the same conditions as when measuring the initial Coulomb efficiency, a half-cell charge-discharge test was performed 10 times, and the discharge capacity was measured. Next, the ratio of the discharge capacity after 10 charge-discharge tests to the initial discharge capacity was calculated and defined as the discharge capacity retention rate.
[0070] Table 1 shows the evaluation results for the initial Coulomb efficiency and discharge capacity retention rate of the half-cell.
[0071] [Table 1]
[0072] Table 1 shows that the half-cells of Examples 1-4 have high initial Coulombic efficiency. Furthermore, the half-cells of Examples 1, 3, and 4 have high discharge capacity retention rates. The half-cell of Example 1 had a discharge capacity retention rate of 94.6% after 20 charge-discharge tests. In contrast, the half-cell of Comparative Example 1 has low initial Coulombic efficiency because the solid electrolyte contained in the negative electrode composite layer is a sulfide solid electrolyte.
Claims
1. A negative electrode composite layer containing a silicon-based active material and a solid electrolyte, It comprises a solid electrolyte layer containing a sulfide solid electrolyte, The solid electrolyte contained in the negative electrode composite layer comprises boron cluster anions and metal cations, but does not contain organic cations, in a solid-state battery.
2. The solid electrolyte contained in the aforementioned negative electrode composite layer is, in general formula Li a (C) b B c H d ) (In the formula, a is an integer between 1 and 5, b is an integer between 0 and 5, c is an integer between 1 and 20, and d is an integer between 1 and 20.) The solid battery according to claim 1, wherein the lithium salt of the carborane anion represented by .
3. The lithium salt of the carborane anion is Li(CB 9 H 10 ) and Li(CB 11 H 12 ), and a molar ratio of Li(CB 11 H 12 ) to Li(CB 9 H 10 ) is more than 0.1 and 10 or less, the solid-state battery according to claim 2.
4. The solid battery according to any one of claims 1 to 3, wherein the negative electrode composite layer contains 20% by volume or more and 80% by volume or less of the solid electrolyte.
5. The solid battery according to any one of claims 1 to 3, wherein the volume ratio of the solid electrolyte to the silicon-based active material in the negative electrode composite layer is 0.40 or more and 7.0 or less.
6. The solid battery according to any one of claims 1 to 3, wherein the negative electrode composite layer further comprises a conductive additive.
7. The solid battery according to claim 6, wherein the volume ratio of the conductive additive to the solid electrolyte in the negative electrode composite layer is 0.010 or more and 0.30 or less.
8. The solid battery according to claim 6, wherein the conductive additive comprises carbon black.
9. The solid battery according to any one of claims 1 to 3, wherein the negative electrode composite layer has a thickness of 10 μm or more and 200 μm or less.
10. The solid battery according to any one of claims 1 to 3, wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.
11. A method for manufacturing a solid battery according to any one of claims 1 to 3, A step of mixing a composition containing the silicon-based active material and the solid electrolyte at a temperature of 120°C or lower to obtain a negative electrode composite material, A method for manufacturing a solid battery, comprising the step of press-molding the negative electrode composite material to form the negative electrode composite layer.
Citation Information
Patent Citations
Manufacturing method of solid electrolyte-containing layer, manufacturing method of solid-state battery, and solid-state battery
JP2022011539A